2020
DOI: 10.15593/perm.mech/2020.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The Numerical study of the influence of a two-scale pore structure on the dynamic strength of water-saturated concrete

Abstract: Many infrastructural concrete facilities, such as dams, bridge footings, foundations of port facilities and offshore drilling platforms, operate in a permanent contact with water. The permeable fractured-porous structure of concrete determines the water-saturated state of the surface layers of such concrete elements. Under dynamic contact loading, the pore fluid is capable of exerting a significant mechanical influence on the local stress-strain state and strength characteristics of the surface layers of concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…The results of modeling the mesoscale samples of fluid-saturated concrete with onescale (capillary) porosity at various values of . ε, η, k, and W confirm the correctness of the assumption [65] that the dynamic compressive strength is a single-valued function of the ratio of the characteristic rates of deformation and fluid flow (Da). Note that the difference (P 2 -P 1 ) in (17) has the meaning of the pressure difference in the center of the sample and on the free side surface in the direction transverse to the loading axis.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…The results of modeling the mesoscale samples of fluid-saturated concrete with onescale (capillary) porosity at various values of . ε, η, k, and W confirm the correctness of the assumption [65] that the dynamic compressive strength is a single-valued function of the ratio of the characteristic rates of deformation and fluid flow (Da). Note that the difference (P 2 -P 1 ) in (17) has the meaning of the pressure difference in the center of the sample and on the free side surface in the direction transverse to the loading axis.…”
supporting
confidence: 63%
“…We were the first to show that the dimensionless parameter Da can be considered a generalization of the conventional dynamic parameter for fluid-saturated high-strength concretes with two-scale pore structure. In a recent paper [ 65 ], we showed that the dependence of dynamic compressive strength of high-strength concrete σ comp on strain rate has a nonlinear (logistic) profile. We discussed the advantage of using the generalized dependence σ comp ( Da ) instead of conventionally used σ comp ( ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations